The Church in India : its mission tomorrow - Hrangkhuma, F.; Kim, Sebastian C. H. (Delhi : ISPCK and Centre for Mission Studies, Union Biblical Seminary, 1996)
Papers presented to two seminars held on 27-29th Jan. 1994 and 12-14th Jan. 1995.
Includes bibliographical references.
Keywords: Christianity -- India -- Congresses; Missions -- India -- Congresses; India -- Church history -- Congresses